Efeito gastroprotetor da 3,6-dimetoxi-6",6"-dimetil-[2",3":7,8]-cromenoflavona isolada de Lonchocarpus araripensis Bentham em camundongos e possíveis mecanismos - Campos, Deive de Andrade (2008)
The flavone, 3,6-dimethoxy-6",6"-dimethyl-[2",3":7,8]-chromeneflavone (DDF) isolated from the roots of Lonchocarpus araripensis Bentham. (syn. Derris araripensis) (Leguminosae), popularly known as angelim, coção or sucupira-branca was evaluated in experimental models of gastric lesions induced by ethanol or indomethacin in mice. DDF, at intraperitoneal doses of 500, 1000 and 2000 mg/kg, failed to produce any signs of overt toxicity or induce mortality in mice. DDF (50, 100 and 200 mg/kg, i.p.) significantly reduced the gastric mucosal lesions evoked by absolute ethanol (0.2mL/animal), in a dose-related manner by 62, 73 e 96% respectively, with an ED50 of 50.87 (38.36-67.46) mg/Kg. DDF (100 and 200mg/Kg, i.p.) also reduced significantly the indomethacin (30mg/Kg, p.o.) -induced gastric lesions, with an ED50 of 65.95 (43.26-100.50) mg/Kg. The gastroprotective mechanism of DDF was analysed against ethanol induced gastric damage at the dose of 100mg/Kg. In animals pretreated with L-NAME (20mg/Kg, s.c.), a nitric oxide synthase inhibitor or glibenclamide (5mg/Kg, i.p.), an ATP-sensitive potassium (KATP) channel blocker, the gastroprotective effect of DDF (100mg/Kg, i.p.) was significantly antagonised, suggesting a role for nitric oxide and demonstrating a likely activation of KATP channels in its gastroprotection. In addition, the gastroprotection afforded by DDF was also significantly reversed in mice pretreated with indomethacin (10mg/Kg, p.o.), a non-selective cyclooxygenase inhibitor or capsazepine (5mg/Kg, i.p.), a transient receptor potential vanilloid receptor 1 (TRPV1) antagonist, thus demonstrating a role for endogenous prostaglandins and suggesting a likely activation of TRPV1 receptors in the gastroprotective effect of DDF. Besides, DDF (100mg/Kg, i.p.) gastroprotection may also be a result of an antioxidant action as evidenced by partial restoration of gastric NP-SH depleted by ethanol. From these results, it is concluded that DDF from Lonchocarpus araripensis roots affords gastroprotection by multiple mechanisms that include an antioxidant action, stimulation of endogenous prostaglandins, nitric oxide synthesis, and the activation of TRPV1 and KATP channels.